2019
DOI: 10.3748/wjg.v25.i26.3392
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes regulated by methylation in colon cancer based on bioinformatics analysis

Abstract: BACKGROUND DNA methylation, acknowledged as a key modification in the field of epigenetics, regulates gene expression at the transcriptional level. Aberrant methylation in DNA regulatory regions could upregulate oncogenes and downregulate tumor suppressor genes without changing the sequences. However, studies of methylation in the control of gene expression are still inadequate. In the present research, we performed bioinformatics analysis to clarify the function of methylation and supply candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 55 publications
3
38
0
Order By: Relevance
“…Over-representation analysis revealed that our gene list was enriched in genes important for developmental and differentiation processes, cell communication, metabolic processes, and regulation of transcription. All of these biological processes are linked to cancer hallmarks, and similar methylation studies focusing on various types of cancer also present gene lists enriched in developmental processes [27], metabolic processes [28] and regulation of transcription [29]. Additionally, we showed that our gene lists contain many non-coding RNA genes, primarily consisting of lncRNAs, suggesting that methylation alterations at non-coding gene promoters are frequently present in cancer.…”
Section: Discussionsupporting
confidence: 69%
“…Over-representation analysis revealed that our gene list was enriched in genes important for developmental and differentiation processes, cell communication, metabolic processes, and regulation of transcription. All of these biological processes are linked to cancer hallmarks, and similar methylation studies focusing on various types of cancer also present gene lists enriched in developmental processes [27], metabolic processes [28] and regulation of transcription [29]. Additionally, we showed that our gene lists contain many non-coding RNA genes, primarily consisting of lncRNAs, suggesting that methylation alterations at non-coding gene promoters are frequently present in cancer.…”
Section: Discussionsupporting
confidence: 69%
“…Microarray technology reveals numerous genes that are activated in different tissues as well as their physiological and pathological statuses and has been regarded as a novel approach for clarifying the mechanisms underlying different diseases[ 10 ]. In recent years with the optimization of gene sequencing platforms, differentially expressed genes (DEGs) have been identified using bioinformatics analyses[ 11 ]. To date, several studies have reported the bioinformatics analysis of IBD using arrays or chips[ 12 , 13 ], but the analysis of UC is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we applied two databases from Gene Expression Omnibus (GEO), GEO2R and online tools for constructing Venn diagrams to identify the DEGs, including upregulated and downregulated genes. Then, the Database for Annotation, Visualization and Integrated Discovery (DAVID) was used to analyze the DEGs based on the molecular function (MF), cellular component (CC), and biological process (BP) and different Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways[ 11 ]. Third, we constructed a protein-protein interaction (PPI) network using Cytoscape and the Molecular Complex Detection (MCODE) app for further analysis.…”
Section: Introductionmentioning
confidence: 99%
“…HCC carcinogenesis is a complex pathological process which associated with speci c tumor genes, multiple signaling cascades as well as epigenetic modi cations [22,23]. In recent years, bioinformatics analyses have been widely used to identify novel diagnostic markers and therapeutic targets for many cancers [24,25], which provide helpful tools for tumor researches. By bioinformatics analyzing, we explored DEGs between HCC tissues and adjacent tumor tissues, based on 3 independent GEO expression datasets in this study.…”
Section: Discussionmentioning
confidence: 99%